Lehman: Premier Branded Talent Syndrome - Sarin, Anil (Prabandhan: Indian Journal of Management, 2009)
These days, the management gurus, economists, politicians, governments and corporate players are debating about the reasons for the downfall of organization like Lehman which used to be Mecca for most of the management graduates from the premier branded management institutions. Many companies formulate their strategies by incorporating the myth that the talent is only available in premier institutions and talent becomes super talent if they pay the executives exorbitant salaries of millions of dollars at even entry level. Interestingly, Lehman was the organization packed with the decision makers equipped with their MBA degrees from the premier business schools in the world. The failure of these executives (who could be termed as premier management talent) raises serious question about the recruitment strategies of many organizations which give revered status to premier branded institutions by offering their students Moon and stars even before letting them to prove their worth and also the deterioration of quality of management education in the premier branded institutions which used to publicize about the placement of their graduates with Lehman and other organizations at exorbitant salaries. This article contributes the innovatory dimensions (with significant focus on premier branded talent and exorbitant salaries), to the whole issue which till now has never been debated/researched intensively and extensively for such corporate failures.